Detecção de podocitúria em pacientes transplantados renais por PCR em tempo real: associação com características clínicas e histopatológicas - Andrade, João Marcelo Medeiros de [UNIFESP] (2018)
Podocyturia has been identified as a prognostic factor in glomerulopathies, it is associated with histological findings characterized as high probability of progression to end stage renal disease. The role of podocyturia in kidney transplantation is unknown. The aim of this study was to evaluate the association between podocyturia and clinical and histological findings of kidney transplanted patients. This is a crosssectional, exploratory and translational study developed at the Instituto de Medicina Integral Prof. Fernando Figueira (IMIP) and at the Translational Research Laboratory A. C. Hart. The following study groups were established according to inclusion and exclusion criteria: renal transplant patients (PTR, n=152), aged between 18 and 70 years, who underwent protocol biopsies at 3 months (PTR3m, n=98) and at 24 months (PTR24m, n=54); negative control volunteers (PCN, n=15) composed by healthy volunteers and a positive control group (PCP, n=15) formed by pregnant women with preeclampsia according to the criteria of the International Society for the Study of Hypertension in Pregnancy (ISSHP), used for polymerase chain reaction (qPCR) validation. Podocyturia was determined by analyzing the messenger RNA (RNAm) expression in the urinary sediment of 5 podocyte-linked genes: NPHS1 (nephrin), NPHS2 (podocin), ACTN4 (alpha-actinin 4), PODXL (podocalyxin) and SYNPO2 (synaptopodin). Our results confirm that gene amplification occurs for ACTN4, SYNPO2, PODXL, NPHS1 and NPHS2 in 151 (99,34%), 151 (99,34%), 93 (61,18%), 81 (53,2%), 76 (50,0%) patients, respectively. The 5 genes expression was increased in the PTR group, compared to the PCN group, NPHS1 8,96x (p<0.0001), NPHS2 9,36x (p<0.0001), ACTN4 8,79x (p<0.0001), PODXL 8,61x (p <0.0001) and SYNPO2 9,12x(p <0.0001). There was no association between gene expression levels and R Alb/cr levels, as well as renal function. The correlation of NPHS2 gene expression levels with R Alb/cr was significant (p=0,003; r=0.38). No significant relationship was found between protocol biopsy findings at 3 months and 24 months with urinary podocytes gene expression. This study shows that there is a higher podocyte urinary loss in kidney transplant patients and that qPCR is a good method to determine podocytes genes expression in urine. The NPHS2 gene expression levels correlate with R Alb/cr levels. However, the analyzed genes cannot be considered as predictive biomarker of active glomerular disease.